1999
DOI: 10.1034/j.1398-9995.1999.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of methods to assess airborne rat and mouse allergen levels. I. Analysis of air samples

Abstract: Airborne laboratory-animal allergens can be measured by several methods, but little is known about the effects of important differences in methodology. Therefore, methods used in research projects in The Netherlands, the UK, and Sweden were compared. Seventy-four sets of three parallel inhalable dust samples were taken by a single operator in animal facilities in the three countries, and analyzed in parallel by the three institutes for rat and mouse urinary allergen. Rat-allergen levels measured by RAST inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 32 publications
1
43
0
3
Order By: Relevance
“…measurements of dust or air samples made by means of RAST inhibition, ELISA inhibition, or polyclonal sandwich assays. [17][18][19][20][21][22] Those studies emphasized the need for improved standardization of assay reagents and allergen standards for optimal exposure assessment. We have developed a polyclonal antibodyebased ELISA for accurate analysis and quantification of the major urinary allergen Mus m 1.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…measurements of dust or air samples made by means of RAST inhibition, ELISA inhibition, or polyclonal sandwich assays. [17][18][19][20][21][22] Those studies emphasized the need for improved standardization of assay reagents and allergen standards for optimal exposure assessment. We have developed a polyclonal antibodyebased ELISA for accurate analysis and quantification of the major urinary allergen Mus m 1.…”
Section: Discussionmentioning
confidence: 98%
“…This study highlighted the need for improved standardization of assay protocols, including dust and air sampling procedures, use of antibodies of defined specificity, and development of allergen standards of known absolute concentration. 21,22 In the United States an enzyme immunoassay for Mus m 1 developed by Ohman et al 3 was used to assess occupational allergen exposure in mouse breeding facilities. This assay was also used in the inner-city asthma studies, which measured allergen levels in homes in 7 US cities.…”
mentioning
confidence: 99%
“…Unfortunately, establishment of an exposure limit is difficult since an adequately standardised assay for quantifying exposure and consequent symptoms is not yet available [26, 27, 28, 29]. The lower limit of 165 U/m 3 , obtained on 22 unloading non-epidemic days in a previous work has been assumed provisionally as the desirable limit under which soybean allergen should be maintained [4].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the dust-sampling method and filter elution are the same for both assays, in this case differences could be due to the immunoassay used. Other comparative studies for the measurement of airborne rat allergen levels have shown that identical air samples would yield different results depending on the assay technology used, with the most important factors being the source and type of antibodies employed [30, 31]. In this study, the different sources of antibodies used could explain some of the differences obtained in the individual concentrations, as demonstrated by Swanson et al [32], in a study of airborne mite allergens using monoclonal antibodies, rabbit polyclonals and human sera as detection antibodies.…”
Section: Discussionmentioning
confidence: 99%